Convolutional encoding and viterbi decoding of data via 5.8GHz wireless LAN in an intelligent urban traffic management system - Juleen L.; Mastan Z.B.K.; Tiong S.K. (2023)
This paper presents an application of convolutional encoding and Viterbi decoding for vehicle traffic data enhancement in an Intelligent Urban Traffic Management System. The 5.8GHz Wireless Local Area Network (WLAN) system is employed, where the traffic data are transmitted among adjacent traffic intersections and a traffic control centre. Environmental factors such as bad weather and noise can critically influence the performance of the wireless link especially in the aspect of Bit Error Rate (BER). A nonsystematic (2, 1, 8) convolutional coding with unique configuration is developed as an error-correction mechanism to reduce the BER. Convolutional code also provides security to the encoded data due to possible unique configuration customization and data can only be retrieved using the matching decoder design. Viterbi decoding is used as it yields the maximum likelihood decoding of the convolutional code. 2005 IEEE.